Fresno County Bar Association's Annual Judges' Dinner at Bob Crossland's Barn - Watkins, Howard::::::::: (1982)
Vickie Savaria checking in Tami Sonder Wilson, Lenore Schreiber, and Judy Soley; John "Nip" Gallagher on right